Analisis kemampuan siswa dalam menyelesaikan soal matematika tipe high order thinking (HOTS) pada materi pola bilangan (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This research aims to find out the learning outcomes, the quality of response regarding the steps on solving the HOTs problems about number pattern among VIII students in Junior High School Sabilina, and factors That Influence Student Learning Outcomes. The method applied in this research is descriptive. The subjects are grade VIII-1 students in Junior High School Sabilina on the Academic Year of 2019/2020. The research was conducted on Februari-Maret 2020 with students’ ability in solving the HOTs problems about number pattern as the object of study The data were collected from the results of written test and interview with some students. The result of this research illustrates that the mastery learning’s percentage of grade VIII students is 25%. The quality of response in solving the problems based on the SOLO taxonomy, based on all the students’ answers alone reflect the fact that the grade VIII students composed of unistructural level (12,5%), multistructural level (75%), and relational level (37,5%). Based on the students’ elucidation and interview, it shows that the understanding of grade VIII students tends to fall on the level of multistructural.
Keywords: HOTs type problems; Number pattern